The battle of the Olympians and the Titans : a retelling - Meister, Cari.; Pellegrino, Richard, 1980- (Mankato, MN : Picture Window Books, 2012)
An illustrated retelling of the classic Greek myth, in which Cronus, the leader of the Titans, battles the Olympians--his children--for power and control of Mount Olympus.
Includes bibliographical references (p. 32).
Library Media Connection starred
Library Media Connection starred, March 2012
3.5
3-6.
3-6
Keywords: Goddesses, Greek -- Juvenile literature; Gods, Greek -- Juvenile literature; Mythology, Greek -- Juvenile literature; Titans (Mythology) -- Juvenile literature; Goddesses, Greek; Gods, Greek; Mythology, Greek; Titans (Mythology); Gods and goddesses; Greek mythology; Titans (Mythology)